(untitled) (Vietnam Journal of Community Medicine, 2022)
Target: Identifying the results of hip hemiarthroplasty for patients ≥ 60 years of age after intertrochanteric crest fractures and/ or femoral neck fractures after 1, 3 and 6 months. Object and method: The uncontrolled intervention study for 76 patients ≥ 60 years of age who have broken intertrochanteric crest and/ or femoral neck and treated in Nghe An Hospital for Traumatology and Orthopaedics by hip hemiarthroplasty. Findings: The ratio of limb inequality < 1 cm is 95.06%; on X-ray film, the ratio of normal physiological surgery is 97.50%; the ratio of dead patients after 6 intervention months is 3.94% (3/76); After 6 months, the number of patients without pain is 94.63%; Ratio of patients who do not need the supporting tools in living activities is 82.16%; Ratio of patients who walk without limitation is 98.63%; After 6 months, the ratio of patients who use stairs normally but do not lean on stairs is 71.23%. The ratio of patients who sit normally on chairs by themselves is 76.71%. The collection result according to the Harris scale at a very high level is 89.04%, high at 9.58%.